Fabrication of electrospinner for producing tube-shaped artificial blood vessels toward treatment applications in cardiovascular diseases - Binh Thanh Vu; Thai Minh Do; Hiep Thi Nguyen (Vietnam Journal of Science, Technology and Engineering, 2022)
Cardiovascular disease stands as a leading cause of high mortality rates in Vietnam and globally. Addressing this, there’s an increasing demand for artificial blood vessels to replace damaged ones in cardiovascular patients. Tissue engineering offers the prospect of replacing damaged blood vessels. Recent advances in science have shown that it is possible to successfully replace human blood vessels. For example, cells can be grown into sheets of tissue to form a layer of vascular cells with impressive strength. Recognizing this need, our team designed a specialized electrospinner machine for crafting artificial blood vessel models. The electrospinner comprises crucial components: a high-power supply source, collectors with tubular structures, and a syringe pump system. This study aimed to (i) construct the electrospinner machine and (ii) assess its operation. Through experimentation, we identified key parameters influencing vascular formation, including DC high voltage source, needle-tip-to-collector distance, needle tip diameter, syringe pump speed, and ambient temperature/humidity. The results demonstrated the machine’s stability and user safety. Optimizing the conditions for vascular fabrication opens avenues for more effective production of artificial blood vessels, potentially revolutionizing cardiovascular treatments and addressing a critical health concern in Vietnam and beyond.